Effect of Transformational Leadership Style, Work Motivation and Work Environment on Employee Performance With Employee Commitment as Intervening Variable (Study on Sub-District in Bondowoso Regency) - Setiawan, Andri; Satoto, Eko Budi; Qomariah, Nurul (International Journal of Management Science and Information Technology, 2022)
This study uses a sampling technique that is non-probability sampling with purposive sampling technique. The purpose of the study was to determine the effect of transformational leadership style, work motivation and work environment on employee performance with employee commitment as an intervening variable. This type of research is a quantitative study of the phenomenon in this study the lack of performance effectiveness that has not yet reached the program realization target. The population in this study were ASN employees in 23 sub-districts of Bondowoso Regency as many as 424 employees. The analysis technique used is the Structural Equation Model (SEM) using WarpPLS 5.0. The test results prove that transformational leadership, work motivation and work environment have a positive and significant effect on employee commitment. The test results prove that transformational leadership, work motivation has a positive and significant effect on employee performance and the work environment has no effect on employee performance. The test results prove that employee commitment has a positive and significant effect on employee performance. The test results prove that transformational leadership, work motivation and work environment have a positive and significant effect on employee performance through employee commitment.